The Essential Oils of Rhaponticum carthamoides Hairy Roots and Roots of Soil-Grown Plants: Chemical Composition and Antimicrobial, Anti-Inflammatory, and Antioxidant Activities. (18th December 2016) - Skała, Ewa; Rijo, Patrícia; Garcia, Catarina; Sitarek, Przemysław; Kalemba, Danuta; Toma, Monika; Szemraj, Janusz; Pytel, Dariusz; Wysokińska, Halina; Śliwiński, Tomasz
Abstract : The essential oils were isolated by hydrodistillation from the hairy roots (HR) and roots of soil-grown plants (SGR) of Rhaponticum carthamoides and were analyzed by GC-MS method. In the both essential oils 62 compounds were identified. The root essential oils showed the differences in the qualitative and quantitative composition. The sesquiterpene hydrocarbons (55–62%) dominated in both essential oils. The major compounds of HR essential oil were cyperene, 13-norcypera-1(5), 11(12)-diene, and cadalene while aplotaxene, nardosina-1(10), 11-diene, and dauca-4(11), 8-diene dominated in SGR essential oil. Both essential oils showed antibacterial activity especially against Enterococcus faecalis (ATCC 29212) and Pseudomonas aeruginosa (ATCC 27853) (MIC value = 125  µ g/mL). HR and SGR essential oils also decreased the expression of IL-1 β, IL-6, and TNF- α and the ROS level in LPS-treatment astrocytes. This is the first report to describe the chemical composition of R. carthamoides essential oil from hairy roots, its protective effect against LPS-induced inflammation and ROS production in astrocytes, and its antimicrobial potential. The results show that R. carthamoides hairy roots may be a valuable source of the essential oil and may be an alternative to the roots of soil-grown plants.